Modern tendencies in diagnostics and treatment of destructive appendicitis - N. A. Maistrenko; P. N. Romashchenko; M. V. Yagin (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The authors analyzed the personal treatment management, which was focused on the priority application of low invasive surgical methods in patients with destructive and complicated appendicitis. MATERIAL AND METHODS. The results of treatment of 803 patients with acute appendicitis were investigated in prospective study. Patients were stratified according to the presence of complicated forms of acute appendicitis and the method of treatment. RESULTS. Laparoscopic appendectomy was performed in 93 % cases and conversion of access was carried out in 6 % cases. The rates of postsurgical complications and wound infection were 1,6 % and 0,7 %, respectively. The indices were lower than in case of open appendectomy 8,4 % and 6,3 % (р < 0,05), respectively. The level of complications was 6 % in application of percutaneous drainage in periappendiceal abscess. Nonsurgical treatment of circumscribed appendiceal mass was effective in 91,9 %. CONCLUSIONS. Realization of given personal approach allowed doctors to use the whole range of minimally invasive techniques in more adequate way. The results of treatment indicated its validity.